Roundup 2020: Agricultural Research Center - Hays (Kansas Agricultural Experiment Station Research Reports, 2020)
Roundup is the major beef cattle education and outreach event sponsored by the Agricultural Research Center - Hays. The 2020 program is the 106th staging of Roundup. The purpose is to communicate timely, applicable research information to producers and extension personnel.
Keywords: Beef cattle; forage